Pengaruh Kecerdasan Emosional terhadap Kinerja Pustakawan di Dinas Perpustakaan dan Kearsipan Kota Padang - Yuliarti, Lidya Noftu; Nurizzati, Nurizzati (Departemen Informasi Perpustakaan dan Kearasipan, 2023)
This research aims to find out how emotional intelligence influences the performance of librarians at the Padang City Library and Archives Service. Emotional intelligence is the ability to feel and understand emotional sensitivity more effectively. Emotional sensitivity can include self-control, the ability to motivate yourself or others, the ability to manage emotions, and the ability to understand other people's feelings effectively, which can be used to guide the brain to make the best decisions. The method in this research is descriptive quantitative. The population of this research was 15 librarians with a sample of 15 respondents. Sampling used total sampling technique. The results of the descriptive analysis show that the influence of emotional intelligence on the performance of librarians in the Padang City Library and Archives Service is 37.3% and there is a positive relationship between emotional intelligence and the performance of librarians in the Padang City Library and Archives Service, which means the higher a person's emotional intelligence. the higher the performance produced.